Antagonistic Activity of Pseudomonas fluorescens Against Curvularia sp. Causing Leaf Spot Disease in Maize - Vivin Andriani; Purity Sabila Ajiningrum; Riza Putri Hanifah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
Maize (Zea mays L.) is an important agricultural commodity in Indonesia, yet its production is often hindered by pathogenic infections, notably Curvularia sp., the causal agent of leaf spot disease. This study aimed to evaluate the antagonistic activity of Pseudomonas fluorescens against Curvularia sp. under in vitro conditions. The pathogenic fungus was isolated from infected maize leaves, while P. fluorescens was isolated from soil samples and identified through biochemical tests and pigment production on King’s B medium. Observations revealed that P. fluorescens produces fluorescent pigments, is an obligate saprophyte, and does not induce soft rot in potato tissue. Antagonism assays showed that the growth of Curvularia sp. was inhibited in the presence of P. fluorescens, as evidenced by fungal hyphae growing away from the bacterial colony. This inhibitory effect is likely due to antifungal secondary metabolites produced by P. fluorescens, including antibiotics, hydrogen cyanide, siderophores, and extracellular enzymes such as chitinase and cellulase, which degrade fungal cell walls. These findings suggest that P. fluorescens holds promise as a biocontrol agent for managing leaf spot disease in maize.   Keywords: Zea mays, Pseudomonas fluorescens, Curvularia sp., antagonism, leaf spot disease